The work of the spirit in redemption and creation : a theological evaluation of influential reformed views - Yoon, Hyung-Chul (Stellenbosch : Stellenbosch University, 2008)
Thesis (MTh (Systematic Theology and Ecclesiology))--Stellenbosch University, 2008.